Analisis Penyebab Pengangguran dan Kesempatan Kerja di Kota Tanjungpinang - Afriyadi; Dewi Asti; Divana Dwi Andini; Kanaya Patrisia; Santi Wulandari (Jurnal Ekonomi Manajemen Dan Bisnis (JEMB), 2025)
The aim of this study is to examine the main causes of unemployment and to assess the opportunities and challenges in creating employment in the city of Tanjungpinang. Unemployment is a complex socio-economic issue with widespread impacts welfare of the community. This study employs a qualitative descriptive method with a literature review approach and uses secondary data obtained from the Central Bureau of Statistics (BPS) and other relevant institutions. The analysis shows that the main causes of unemployment in Tanjungpinang include a mismatch between the skills of the workforce and labor market demands, uneven economic growth, and limited development of local industries and investment. On the other hand, employment opportunities can be improved through the development of the tourism sector, MSMEs, and the creative economy, supported by relevant job training programs. This study indicates the importance of collaboration between local authorities, the business sector, and educational institutions to build an inclusive and sustainable employment ecosystem.